Faktor-faktor Penyebab Kesenjangan Antara Mahasiswa Urban Katolik dengan Gereja Di Kota Malang Ditinjau Dari Model Praksis Stephen B. Bevans - Stevanus, Adolvus (Perspektif, 2023)
This article discusses the gap that occurs between Catholic Urban Students and the Church in Malang City. This writing uses qualitative research methods with direct interviews with several urban Catholic students. The author dis[1]cusses this theme in the light of the praxis model according to Stephen B Bevans. The results of this research found that there are two factors that cause the gap between urban Catholic students and the Church. The first factor comes from urban students, namely urban students do not understand the meaning of the Eucharist celebration well, so for them the Eucharist is not an obligation, but as a necessity, urban students often come late to church and choose seats at the back so they don’t hear well. clear parish information is read at the time of the announcement. Then urban students still haven’t moved on with the old culture that comes from their region, but they are swept away by digital culture. The second factor comes from the church. By leading the Eucharist celebration on Sunday, the parish priest feels he has carried out his obligation to serve the people as a whole. Then the pastoral method is not based on the reality of people’s lives so that the services provided by pastoral officers do not touch directly with the lives of people (urban students). Based on the results of this research, this research recommends that the church be the first initiator in embracing Urban Catholic students in Malang City by accommodating activities or training and providing opportunities for them to be involved in church services and supporting them in the growth and development of their spiritual life.